Cell fusion induced by the murine leukemia virus envelope glycoprotein. - Jones, J S (1993)
To determine whether ecotropic murine leukemia virus (MuLV) envelope glycoproteins are sufficient to cause cell-to-cell fusion when expressed in the absence of virus production, we used an ecotropic MuLV, AKV, to construct env expression vectors that lack the gag and pol genes. The rat cell line XC, which undergoes cell-to-cell fusion upon infection with ecotropic MuLV, was transfected with wild-type env expression vectors, and high levels of syncytium formation resulted. Transfection of the murine cell line NIH 3T3 with expression vectors containing the wild-type or mutated env region did not result in syncytium formation. Immunoprecipitation analysis of the envelope glycoproteins expressed in NIH 3T3 and XC cells showed that the mature surface glycoprotein expressed in XC cells was of a much lower apparent molecular weight than that expressed in NIH 3T3 cells. Further characterization showed that most if not all of this difference was the result of differences in glycosylation. Finally, site-directed mutagenesis was used to introduce several conservative and nonconservative changes into the amino-terminal region of the transmembrane protein. Analysis of the effect of these mutations confirmed that this region is a fusion domain.